Media sebagai Aparatus Ideologis: Representasi Muslim dan Produksi Identitas Kewarganegaraan - Fresyam Antika Ajeng (Sekolah Tinggi Agama Islam Taruna Surabaya, 2026)
This study examines how mass media function as an ideological apparatus in representing Muslims and producing citizenship identity in Indonesia. Employing a qualitative approach within a critical paradigm and Fairclough’s Critical Discourse Analysis model, the research analyzes selected national online media coverage addressing Islamic-related socio-political issues. The findings reveal four dominant representational patterns: securitization, normative moderation, politicization of identity, and commodification of religiosity. These patterns not only shape public images of Muslims but also interpellate them into selective and conditional forms of citizenship. The media construct a symbolic standard of the “ideal” Muslim citizen moderate, stable, and compatible with market logic while positioning alternative expressions of religious identity in ambivalent or problematic terms. The study demonstrates that citizenship is not merely a legal-formal status but is discursively produced through media representation. This research contributes to media and citizenship studies by highlighting representation as a mechanism of subject formation within contemporary democracy.